Shifts in euro area Beveridge curves and their determinants - Boele Bonthuis; Valerie Jarvis; Juuso Vanhala (Bank of Finland, 2015)
This paper analyses euro area Beveridge curves at the euro area aggregate and country level over the past 25 years. Using an autoregressive distributed lag model we find a significant outward shift in the euro area Beveridge curve since the onset of the crisis, but considerable heterogeneity at country level. We test for factors underlying these developments using the local projections method of Jordà (2005). Skill mismatch, high shares of workers in the construction sector, as well as high pre-crisis financial slack and home ownership rates appear strong determinants of outward shifts in Beveridge curves in response to a negative shock. Higher female participation rates mitigate these effects.
URN:NBN:fi:bof-201502031042
Keywords: J62; J63; E24; E32; 330; Beveridge curve; crisis; mismatch; unemployment; labour shortages; vacancies